A Microcurrent Dressing Reduces Cutibacterium Acnes Colonization in Patients Undergoing Shoulder Arthroplasty or Arthroscopy: A Prospective Case Series. Issue 1 (February 2023) - Miller, Bruce S.; Olszewski, Adam M.; Bedi, Asheesh
Background: Cutibacterium acnes infections in the shoulder remain a significant concern in the setting of shoulder arthroplasty. Purpose : We sought to evaluate the efficacy of a microcurrent dressing in reducing C. acnes skin colonization and thereby reducing the risk of periprosthetic joint infection of the shoulder. Methods : This study was designed as a prospective case series. From October 2017 to February 2019, patients undergoing elective shoulder arthroplasty or arthroscopic shoulder surgery at a major academic medical center were offered enrollment; they signed an informed consent to participate. Patients under the age of 18, scheduled for revision shoulder arthroplasty, or with sensitivity or allergy to silver, zinc, or latex were excluded. Subjects underwent skin culture swab of the shoulder in the mid-point of the planned deltopectoral incision. The JumpStart (Arthrex; Naples, FL) microcurrent dressing was then placed over the area of the planned incision, and a full-thickness skin biopsy was harvested from the incision at the initiation of the surgical procedure. All specimens were cultured for C. acnes by the hospital's clinical microbiology laboratory with standard anaerobic technique. Results : Thirty-one subjects were enrolled in the study. Those who demonstrated no growth at baseline for the control specimen were excluded from further analysis (N = 11), given the absence of preoperative C. acnes colonization. Culture results from the 20 remaining subjects revealed significantly diminished C. acnes skin growth at the time of surgery compared to baseline. Sixty percent (12 of 20) of the subjects with positive skin swabs at baseline demonstrated no growth in the skin biopsy specimens at the time of surgery. There were no adverse events associated with the application of the microcurrent dressing. Conclusion : This prospective case series found that preoperative application of a microcurrent dressing resulted in significantly diminished C. acnes skin burden at the time of surgery in patients undergoing elective shoulder arthroplasty or arthroscopic shoulder surgery. Further study is warranted to investigate whether this preoperative intervention may contribute to a reduction in perioperative infections, including prosthetic joint infection.